Investigation of Harmonic Effect in Turkey's Iron - Steel Industry - Kekezoglu, B.; Kocatepe, C.; Yumurtaci, R.; Arikan, O.; Baysal, M.; Bozkurt, A.; Akkaya, Y.; Ozdemirci, E. (IEEE, 2008)
Power quality is a considerable concern for power systems. The voltage-current characteristics of iron and steel industries are unsteady and especially in these industries nonlinear loads cause power quality problems. High power steel plants produce three-phase unbalanced operation, flicker and harmonics. This paper presents field measurement results of several steel industries in Turkish Electrical Power System. Also, the effects of these industries on power quality disturbances are investigated. Plant measurements are taken by members of the National Power Quality Project in Turkey. This project is supported by The Scientific and Technological Research Council of Turkey with reference number of 105G129.
Keywords: Power quality; iron-steel industries; arc furnaces; harmonic; Energy & Fuels; Engineering